Globular Cluster UVIT Legacy Survey (GlobULeS) – II. Evolutionary status of hot stars in M3 and M13. Issue 1 (5th April 2023) - Kumar, Ranjan; Pradhan, Ananta C; Sahu, Snehalata; Subramaniam, Annapurni; Piridi, Sonika; Cassisi, Santi; Ojha, Devendra K
ABSTRACT: We present a far-ultraviolet (FUV) study of hot stellar populations in the second parameter pair globular clusters (GCs) M3 and M13, as a part of the GC UVIT Legacy Survey programme (GlobULeS). We use observations made with F148W and F169M filters of the Ultraviolet Imaging Telescope (UVIT) onboard AstroSat along with ground-based data (UBVRI filters), Hubble Space Telescope ( HST ) GC catalogue, and Gaia EDR3 catalogue. Based on the FUV-optical colour–magnitude diagrams, we classify the sources into the horizontal branch (HB) stars, post-HB stars, and hot white dwarfs (WDs) in both the GCs. The comparison of synthetic and observed colours of the observed HB stars suggests that the mass-loss at the red giant branch and He spread in both clusters have a simultaneous effect on the different HB distributions detected in M3 and M13, such that HB stars of M13 require a larger spread in He (0.247–0.310) than those of M3 ( Y  = 0.252–0.266). The evolutionary status of HB stars, post-HB stars, and WDs are studied using SED fit parameters and theoretical evolutionary tracks on the H–R diagram. We found that the observed post-HB stars have evolved from zero-age HB (ZAHB) stars of the mass range of 0.48−0.55 M⊙ in M3 and M13. We detect 24 WD candidates in each cluster having ${\rm \log ({\it L}_{bol}/L_\odot)}$ in the range of −0.8 to +0.6 and ${\rm \log ({\it T}_{eff}/K)}$ in the range of 4.2–5.0. Placing the WDs on the H–R diagram and comparing them with models, it is found that M13 has a population of low-mass WDs, probably originating from binary evolution.